Effect of metal conditioners on the adhesive bonding of resin cements to cast titanium - da Rocha, Sicknan Soares; Adabo, Gelson Luis [UNESP]; Spinola, Sandra Gouveia [UNESP]; Fonseca, Renata Garcia [UNESP]; Ferreira, Anelise Rodolfo [UNESP] (My University, 2007)
Objective: To assess the effect of metal conditioners on the bond strength between resin cements and cast titanium. Method and Materials: Commercially pure titanium (99.56%) was cast using an arc casting machine. Surfaces were finished with 400-grit silicon carbide paper followed by air abrasion with 50-µm aluminum oxide. A piece of double-coated tape with a 4-mm circular hole was then positioned on the metal surface to control the area of the bond. The prepared surfaces were then divided into 4 groups (n=10): G1, unprimed Panavia F; G2, Alloy Primer-Panavia F; G3, unprimed Bistite DC; G4, Metaltite- Bistite DC. Forty minutes after insertion of the resin cements, the specimens were detached from the mold and stored in water at 37°C for 24 hours. Shear bond strength was performed in a testing machine (MTS 810) at a crosshead speed of 0.5 mm/min. Data were analyzed using ANOVA and Tukey’s test with a .05 significance level. The fractured surfaces were observed through an optical microscope at 10× magnification. Results: The G1 group demonstrated significantly higher shear bond strength (17.95 MPa) than the other groups. G3 (13.79 MPa) and G4 (12.98 MPa) showed similar mean values to each other and were statistically superior to G2 (9.31 MPa). Debonded surfaces generally presented adhesive failure between metal surfaces and resin cements. Conclusion: While the Metaltite conditioner did not influence the bond strength of the Bistite DC cement, the Alloy Primer conditioner significantly decreased the mean bond strength of the Panavia F cement. © 2007 by Quintessence Publishing Co Inc.
Keywords: Fixed partial denture; Metal conditioners; Resin cements; Shear bond strength; Titanium